Use of probiotics instead of antibiotics in broiler production (Progressive Agriculture, 2019)
Effects of different available commercial probiotics on growth performance and blood parameters were evaluated. To achieve the objectives, a total of 198 one-day-old Hubbard Isa Starbro broiler chicks were raised over 28 days. Chicks were wing-banded, weighed individually and randomly allocated into six equally major groups each having three replicates. Broilers of group T1 (control group) were fed the starter and finisher diets. The broilers of groups T2 was fed the control starter and finisher diets supplemented with antibiotic and groups T3-T5 were fed 4 different commercially available probiotics (T3-Guardizen-M, T4-Protexin and T5-Poultry star sol in drinking water. Weekly body weight, feed consumption and feed conversion were recorded during experimental period. Blood parameters at 4 weeks of age including packed cell volume (PCV), haemoglobin (Hb), total protein, albumin, triglycerides, high density lipoprotein (HDL), uric acid, cholesterol, glucose, intestinal microflora, pH and color properties of meat were determined. All birds were kept under similar environmental, managerial and hygienic conditions. Probiotic supplementation significantly increased the body weight and daily weight gain of broiler chicks at 28 days (p 0.05). The lower percent of abdominal fat and the higher percent of dressed carcass, breast and thigh were observed in experimental probiotic(s) groups. pH and meat color did not affect among treatments. There was lower mortality rate in probiotics among groups. Moreover, there was no significant change for Hb, PCV, total protein and albumin concentrations among different groups. Also, total protein, lipids and albumin concentrations were not affected by probiotic(s) supplementation. In addition, different probiotics showed a significant decrease (p